Joan Maragall: creació, traducció i reescriptura - Ardolino, Francesco (Studia Romanica Posnaniensia, 2021)
What is the role of translation in Maragall’s work? If his first goal was to bestow cultural support to Catalan literature with the addition of the European authors of Modernism, the second stage of the Catalan poet’s agenda becomes more ambitious, delving into the origins of Western literature and culminating in the translation of the Homeric Hymns. My contribution analyzes how, on the one hand, the Catalan rewriting of the works of Nietzsche, Goethe, Novalis, or Dante draws a progressive and continuous line within Maragall’s ideas; and, on the other hand, what impact these versions have on his own literary creation, through the loanwords that spread across his translations, and his poetry.